Les mines métallifères du département de la Loire. Bilan de sept années de recherches - François Dumoulin (Revue Archéologique du Centre de la France)
This study is intended to show the results of the metal mining heritage within the limits of the department of the Loire. From different sources (place names, mentions in archives, reports of working operations and geological literature), a first analysis identifies 63 potential sites grouped into two concessions. Prospecting enabled us to find 32 of them and draw up an inventory. It must be remembered that underground works are very rarely preserved. However we picked up numerous small scale surface workings connected with the search for galena for potters.